Apakah Keterlekatan Kerja Mampu Memediasi Dukungan Lembaga Terhadap Kinerja Karyawan? - Marhisar Simatupang; Lania Muharsih; Debi Angelina Barus; Aisyah Ratnaningtyas (unprimdn.ac.id, 2022)
This research able to knowing the role of organizational support on work performance mediated work engagement. The variables tested in this study are organizational support as exogenous variables, work engagement and work performance as endogenous variables. The research respondents were autism therapists at institutions for children with special needs in Karawang, totaling 203 therapists. Data analysis used Structural Equation Model (SEM) using partial least squares (PLS). Based on the results of the hypothetical model test, organizational support influences work performance mediated by work attachment. This means that the research theoretical model can be accepted as a model that fits the data in the field. This also shows that the stronger the employee gets support from the organizational and the employee understands the employee's work engagement will increase. The yield from these findings able to use consideration to handle increased employee work engagement at the Institute.